Short Communication: A rapid survey of herpetofauna diversity in Bama coastal forest at Baluran National Park, Indonesia - ARIF MOHAMMAD SIDDIQ; RETNO WIMBANINGRUM; HARI SULISTIYOWATI; RENDY SETIAWAN; ALVAN SETIAWAN; NANANG DWI WAHONO (Society for Indonesian Biodiversity, 2024)
Abstract. Siddiq AM, Wimbaningrum R, Sulistiyowati H, Setiawan R, Setiawan A, Wahono ND. 2024. Short Communication: A rapid survey of herpetofauna diversity in Bama coastal forest at Baluran National Park, Indonesia. Biodiversitas 25: 2323-2329. Scientific reports on herpetofauna in Baluran National Park (BNP) are still limited. Meanwhile, several geographical areas, such as the Bama Baluran National Park coastal forest, have potential herpetofauna diversity within this conservation area yet to be reported. Therefore, this study aimed to determine the diversity of herpetofauna species in BNP's Bama coastal forest (BCF). The method was conducted using the Visual Encounter Survey (VES) in three tracks, conducted by combining Time Restricted Search (TRS) or using observation time for five hours during the mid-afternoon (06.00 AM-11.00 AM) and four hours at night (07.00 PM-11.00 PM) on each track. This study recorded 17 herpetofauna species, comprising 6 amphibian and 11 reptile species, in the BCF of Baluran National Park. The diversity index of herpetofauna species in this area was moderate category (H’=2.25). Species Fejervarya limnocharis Gravenhorst 1829 (38 individuals) has the highest abundance in the BCF and was found in track 1 (swamp area). Meanwhile, three species have the lowest abundance, such as Kaloula baleata Müller 1836, Microhyla palmipes Boulenger 1897, and Cryptoblepharus balinensis Barbour 1911, with 1 individual in each species.